Perancangan Website Pelayanan Klien dan Pra-Pendaftaran Perkara di Kantor Hukum Kofipindo - Cici Pratiwi; Zaskia Maghfira (Saturnus: Jurnal Teknologi dan Sistem Informasi, 2026)
This research aims to design and build a client service website and pre-registration of cases at the KOFIPINDO Law Office as a solution to administrative problems that are still carried out manually. The system is developed using the waterfall method through the stages of needs analysis, system design, coding, testing, and maintenance. The website that was built provides features for account registration, filling in case data, uploading supporting documents, and verification by the admin so that the file is ready to be submitted to the e-Court system. In addition, the system is equipped with a case status monitoring dashboard, automatic notifications to clients, and submission history that can be accessed at any time. The results of the study show that this platform is able to improve service efficiency, minimize administrative errors, and speed up the pre-registration process of cases. The implementation of this system also helps to increase the transparency of communication between law firms and clients. Furthermore, the use of this website has the potential to reduce the administrative workload of staff, optimize the management of case data, and improve the accuracy of legal documentation. The system is also designed with the client's data security and privacy aspects in mind in accordance with the principles of digital information protection. Thus, this system can be an effective, structured, and integrated digital means to support the modernization of legal services at KOFIPINDO, improve service professionalism, and strengthen the competitiveness of law offices in the digital ecosystem.